1997
DOI: 10.1542/peds.99.2.216
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is a Useful Marker for Guiding Duration of Antibiotic Therapy in Suspected Neonatal Bacterial Infection

Abstract: We conclude that CRP could be a key parameter for individually guiding the duration of antibiotic treatment in a major subgroup of newborns with suspected bacterial infection. This approach would allow considerably shorter courses of antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
103
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 15 publications
11
103
2
9
Order By: Relevance
“…Alguns trabalhos também mostraram fatos semelhantes e, por vezes, incluíam essas crianças no grupo daquelas com sepse comprovada 7,21,26 .…”
Section: Discussionunclassified
“…Alguns trabalhos também mostraram fatos semelhantes e, por vezes, incluíam essas crianças no grupo daquelas com sepse comprovada 7,21,26 .…”
Section: Discussionunclassified
“…2005, that were maintained in the publication of the surviving sepsis campaign of Delinger and cols., 2012) associated with reactive C protein greater than 10 mg/dL (10)(11)(12)(13)(14) were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Duration of sepsis was classified as sepsis of short duration (Group A) by the presence of clinical and laboratory signs until the 8 th day of evolution and prolonged sepsis (Group B) when signs were observed beyond the 8 th day of evolution (13). Cure was considered when clinical and laboratory variable of sepsis were absent and reactive protein C was lower than 10 mg/dL (12,14,15).…”
Section: Methodsmentioning
confidence: 99%
“…18 Yentis SM et al and Ellis S et al showed that measurement of CRP can be used to monitor the antibiotic therapy and that successful antibiotic therapy lowered CRP levels. 19,20 As a summary, this study has thrown up positive results regarding the utility of CRP in burn patients. The CRP values correctly predict sepsis in majority of the patients.…”
Section: Discussionmentioning
confidence: 82%